Strain sebagai pendorong mahasiswa menggunakan pinjol ilegal: Analisis viktimisasi mahasiswa korban pinjol ilegal - Logan Gunadi Wirawan (Journal of Environment and Geography Education, 2024)
Background: The cases range from socialization that requires students to participate in using online loans, to murders with the motive of paying for online loans. Illegal online loans cases continue to push the urgency of research that analyzes why many students become users of illegal online loans. Findings: Although the number of students using illegal online loans continues to increase, the victimization experience of students using illegal online loans is still very little researched. Student status places someone as an academic, someone who is highly educated and has critical and analytical thinking skills. Methods: This study uses a critical criminology method with the use of a qualitative approach to produce strain analysis. This study uses data mining with a qualitative approach with a structured interview methodology. This study also found that the impact of illegal online loans on students is very disruptive to their lives on a large scale and in the long term. Conclusion: Students experience losses from the burden of illegal online loan costs which are very large because financial exploitation through interest and hidden fees is very large due to their limited financial capabilities. The magnitude of financial losses from illegal online loans greatly disrupts students' academic lives. Many students have to drop out of college due to limited funds or because they have to focus on finding income to cover the financial losses from illegal online loan exploitation. The terror, intimidation, threats, and violence experienced by students disrupt their mental and physical health. Students have to live in conditions without security for a long period of time when they become users of illegal online loans. Many students who are victims of illegal online loans suffer from mental disorders that interfere with their ability to live their lives. Long-term student recovery requires psychiatric care that takes a lot of effort, time, and money.